Addressing Low Speaking Proficiency in EFL Students: The Impact of Integrated Teaching Strategies in an Islamic Education Setting - Usman, Abdurrahman Hi.; Mahmud, Adi F. (International Journal of Language Education, 2024)
The primary aim of this study was to address the challenges of low speaking proficiency and motivation among second-year students in an Islamic education university department. This was achieved by implementing an integrated teaching strategy within a Classroom Action Research (CAR) framework to enhance students' speaking skills and active involvement in the learning process. The study employed a CAR design, conducted over two cycles. Each cycle comprised four stages: planning, action, observation, and reflection. The intervention involved an integrated teaching strategy that combined multiple language skills—listening, speaking, reading, and writing—within a cohesive instructional framework. Data were collected through post-tests, observation checklists, and reflection notes. Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative data were examined through thematic analysis. The results demonstrated significant improvements in both speaking performance and student engagement between Cycle 1 and Cycle 2. In Cycle 1, the majority of students scored in the "Fair" category, with only 24.39% achieving "Good" scores. Following strategic adjustments, Cycle 2 saw a marked increase in average post-test scores, with 87.80% of students meeting or exceeding the success criteria. The level of active involvement also rose significantly, reflecting the effectiveness of the revised integrated strategy. The findings highlight the value of integrated language instruction and the importance of iterative refinement in teaching methodologies. This study contributes to the theoretical understanding of language acquisition and offers practical insights for EFL educators, particularly in contexts where students face challenges in developing speaking proficiency. The study underscores the need for creating supportive and engaging learning environments that foster student participation and language development.This study provides empirical evidence supporting the effectiveness of integrated teaching strategies in EFL contexts, particularly within Islamic education settings. It demonstrates how Classroom Action Research can be utilized to improve teaching practices and student outcomes continuously. The research offers a model that can be adapted and applied in similar educational contexts to enhance language learning.